2002
DOI: 10.5380/raega.v6i0.18516
|View full text |Cite
|
Sign up to set email alerts
|

Uma evaluación de los efectos del aislamiento, La topografia, los suelos y El estatus de protección sobre las tasas de deforestación em México

Abstract: Un mapa de deforestación del território mexicano, derivado de Ia sobreposición de dos cartografias de uso del suelo y vegetación de 1993 y 2000, se comparo con variables espaciales como el aislamiento (distancias a Ias carreteras y a Ias poblaciones), Ia topografia (altitud y pendiente), el tipo de suelos y el estatus de protección (dentro de una ANP o fuera) en un sistema de información geográfica (SIG). Para evaluar Ia relación entre Ia deforestación y estas variables explicativas, se Ilevaron a cabo algunas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In an analysis conducted by Mas et al (2003), regarding the different factors affecting forest maintenance in a nationwide study, they concluded that the effect of protected area status on deforestation was actually very weak, and rather that deforestation was strongly correlated to remoteness, topography and soil type. In a subsequent LUCC study, Mas (2005) evaluates the effectiveness of the Calakmul Biosphere Reserve (CBR) in protecting forests.…”
Section: Discussionmentioning
confidence: 96%
“…In an analysis conducted by Mas et al (2003), regarding the different factors affecting forest maintenance in a nationwide study, they concluded that the effect of protected area status on deforestation was actually very weak, and rather that deforestation was strongly correlated to remoteness, topography and soil type. In a subsequent LUCC study, Mas (2005) evaluates the effectiveness of the Calakmul Biosphere Reserve (CBR) in protecting forests.…”
Section: Discussionmentioning
confidence: 96%
“…This is due to the fact that insecurity in tenure often encourages unrestricted access to land without clear allocation, forest clearing and land grabbing (Angelsen et al 2013). A comprehensive evaluation of the effectiveness of the PA in the region should consider such socioeconomic contexts, including suitability of lands for developing economic activities (Mas et al 2003;Mas et al 2005;Duran-Medina et al 2001), land tenure and management practices (Hodgdon et al 2015;Bullock et al 2019;Vaca et al 2019), historical processes and strength of institutional capabilities (Bruner et al 2001;Brechin 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Aunque es posible que el CUS no muestre un pa-trón específico, en general, las altitudes intermedias fueron las más afectadas. Algunos trabajos han encontrado que la altitud pudiera estar relacionada de manera directa con la deforestación en México, donde a mayor altitud, aumenta la pérdida de bosque (Mas et al 2002;Pineda-Jaimes et al 2009), aunque no es del todo claro si se trata de una combinación altitud-pendiente (Mas et al 1996). Dentro de la FVT, por abajo de la cota altitudinal de los 2,800 m, en general se observa marcadamente el efecto del deterioro por actividades antrópicas (Villers et al 2006).…”
Section: Discussionunclassified